Canine diabetes mellitus demonstrates multiple markers of chronic inflammation including Th40 cell increases and elevated systemic-immune inflammation index, consistent with autoimmune dysregulation - Vaitaitis, Gisela; Webb, Tracy; Webb, Craig; Sharkey, Christina; Sharkey, Steve; Waid, Dan; Wagner, David H. (Frontiers in Immunology, 2024)
Canine diabetes mellitus (CDM) is a relatively common endocrine disease in dogs. Many CDM clinical features resemble human type 1 diabetes mellitus (T1DM), but lack of autoimmune biomarkers makes calling the disease autoimmune controversial. Autoimmune biomarkers linking CMD and T1DM would create an alternative model for drug development impacting both human and canine disease. We examined peripheral blood of diagnosed CMD dog patients comparing it to healthy control (HC) dogs. Differences in adaptive immune lymphocytes, innate immune macrophages/monocytes and neutrophils and differences in platelets were detected. Differences in serum glucose, cholesterol and the liver function enzyme alkaline phosphatase were detected. Markers of disease progression such as glycated albumin (fructosamine) and c-peptide were addressed. Significant differences in lymphocytes, monocytes, and platelets were found, with increased neutrophils occurring in CDM. A systemic immune inflammation index (SII) and chronic inflammation index (CII) as measures of dynamic changes in adaptive and innate cells between inflammatory and non-inflammatory conditions were created with highly significant differences between CDM and HC. Th40 cells that are demonstrably pathogenic in mouse T1DM and able to differentiate diabetic from non-diabetic subjects in human T1DM were significantly expanded in peripheral blood mononuclear cells. The association of significantly elevated Th40 cells in CDM when compared to HC or to osteoarthritis, a chronic but non-autoimmune disease, suggests peripheral blood Th40 cell numbers as a biomarker that reflects CDM chronic inflammation. The differences in SII and CII further underscore those findings.